2016
DOI: 10.1146/annurev-biophys-070915-094206
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles of Length Control of Cytoskeletal Structures

Abstract: Cells contain elaborate and interconnected networks of protein polymers, which make up the cytoskeleton. The cytoskeleton governs the internal positioning and movement of vesicles and organelles and controls dynamic changes in cell polarity, shape, and movement. Many of these processes require tight control of the size and shape of cytoskeletal structures, which is achieved despite rapid turnover of their molecular components. Here we review mechanisms by which cells control the size of filamentous cytoskeleta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 55 publications
2
100
0
Order By: Relevance
“…Our analysis describes the limitations associated with the limiting-pool mechanism and underlines the necessity for the cell to invest in additional mechanisms to control size. In fact, there are other length-sensing mechanisms that have been reported in the filament literature (Andrianantoandro and Pollard, 2006; Chesarone-Cataldo et al, 2011; Gardner et al, 2011; Marshall et al, 2005; Mohapatra et al, 2015, 2016; Varga et al, 2006). In these studies specific proteins have been identified as being critical to length-control, and found to either modulate the assembly or the disassembly rate of cytoskeletal filaments in a length dependent fashion (Mohapatra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis describes the limitations associated with the limiting-pool mechanism and underlines the necessity for the cell to invest in additional mechanisms to control size. In fact, there are other length-sensing mechanisms that have been reported in the filament literature (Andrianantoandro and Pollard, 2006; Chesarone-Cataldo et al, 2011; Gardner et al, 2011; Marshall et al, 2005; Mohapatra et al, 2015, 2016; Varga et al, 2006). In these studies specific proteins have been identified as being critical to length-control, and found to either modulate the assembly or the disassembly rate of cytoskeletal filaments in a length dependent fashion (Mohapatra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this mechanism is unable to maintain multiple structures that have a well-defined size, which assemble from a common pool of subunits. Cells can get around this problem by using additional size-regulatory mechanisms (Mohapatra et al, 2016). Quantitative experiments that measure the size and assembly dynamics of intracellular structures, and how they vary with different parameters, like the total amount of the limiting subunit or the size of the chamber within which they are assembled, are needed to quantitatively define the role of the limiting-pool mechanism in regulating size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a direct result of resource limitation and does not rely on the existence of a motor density gradient, as necessary for domain wall localization in the presence of unlimited resources [20][21][22][23]. So far, most work on the role of limited resources has focused on single components of the relevant system [17][18][19][24][25][26][27][28]. Only a few studies have considered simultaneous limitation of two resources [29].…”
mentioning
confidence: 99%
“…Several mechanisms have been proposed that add effective cooperativity to these one-dimensional structures through length-dependent arrival of specialized molecules that modify the dynamics [23]. A thermodynamic analysis of these systems raises additional challenges beyond those produced by the intrinsic cooperativity of higher-dimensional models, because the energetics of the underlying molecular motor transport and enzyme activity would also have to be explicitly accounted for.…”
Section: Discussionmentioning
confidence: 99%